Delayed Recognition of a Rare Mediastinal Lymphoma Presenting as Postpartum Circulatory Collapse - Jasmina Kevric; Sanil Nair; David Ernest (Hindawi Limited, 2014)
We report a case of a 29-year-old primigravida at 36 weeks of gestation following an emergency caesarean section, complicated by respiratory distress and multiorgan failure secondary to superior vena cava (SVC) obstruction, requiring intubation and prolonged ventilatory support. The presented case highlights the consequences of delayed recognition of SVC obstruction due to a reluctance to undertake appropriate radiological imaging during pregnancy.